HUBUNGAN FREKUENSI PEMBERIAN ASI TERHADAP KEJADIAN IKTERUS FISIOLOGIS PADA BAYI BARU LAHIR DI SEMEN PADANG HOSPITAL TAHUN 2017 - -, Delvi Dasnur*, Ira Mulya Sari (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Based on the results of the interview date march 5, 2017 with the babys mother is 10people, 3 people there mother giving baby breast milk frequency 5 times a day by reason ofbreast milk has not come out, 3 people mother gives the breast milk with a frequency of sixtimes a day by reason of breast milk is still a bit 2 people didn’t give breast milk and infantformula only gives on her baby with al san insufficent breast milk and breast milk frequencyaverage 8-12 times a day for 5 to 15 minutes. The purpose of knowing the frequencyrelationship of breast feeding with physiological jaundice in the newborn in the spital the year2017 padang cement.Type of this research is Descriptive Analytic with Cross Sectional Study. Researchconducted at semen padang hospital neonatology unit. Date retrieval is done for a month on 1-30 july 2017. Entire population of newborn in semen padang hospital as much as 41 babies.Samples taken using total sampling amounted to 41 babies. By means of observation and usingquestionnaires, then in the analysis with a statistical test of Chi-Square.The results showed more than mother separoh (56,1%) providing breast milk for lessthan 8 times a day more than the baby’s separoh (61,0%) experience the physiologicaljaundice incident. Statistically it can be concluded that there is a meaningful relationshipbetween the frequency of breast feeding with physiological jaundice infants p-value≤ 0.005.Nurses and midwives are expected along with other health care personnel can provideinformation or guidance that is complete on about the importance of breast feeding on in fants,including consequences if the baby does not get breast milk.